Research on multi-AP joint transmission scheme based on improved genetic algorithm - Man LIU; Xuming FANG (物联网学报)
In order to solve the problem that overlapping basic service set (OBSS) users are subject to serious co-frequency interference in the dense Wi-Fi network, resulting in low signal to interference plus noise ratio (SINR) of received signals, low data transmission rate or inability to transmit, a multi-access point (AP) joint transmission (JT) scheme based on improved genetic algorithm (IGA) selection of AP coordination set was proposed.Firstly, the SINR threshold method was used to divide all station (STA) in the system into central users and edge users, and the JT scheme was adopted for edge users.Then, with the goal of maximizing the throughput of edge users, IGA was proposed to determine the appropriate coordinated AP for each edge user to form its own AP coordination set, and maximize the potential gain of JT technology.The simulation results show that the proposed scheme can effectively reduce the co-frequency interference between BSS and improve the performance and throughput of BSS edge users in dense network.